The Impact of Natural Gas Revenue on Economic Growth in Tanzania - Kondowe, Gerald; Osoro, Nehemiah (Tanzania Journal for Population studies and Development, 2022)
This article investigates the linkage between natural gas revenue and economic growth in Tanzania from 2005q1 to 2017q2 periods. The study uses unit root analysis, Gregory Hansen (GH) cointegration test, autoregressive distributed lag (ARDL) bound cointegration test, and the error correction model (ECM). The Zivot and Andrews (ZA) and Clemente-Montares-Reyes (CMR) unit root tests reveal that the series had a mixed order of integration, i.e., I(0) and I(1) with a single structural break. The GH cointegration test suggests that the break date is 2012q1. Both GH and ARDL bound cointegration tests indicate that a long-run relationship exists. The empirical results show that natural gas revenues stimulate economic growth in Tanzania both in the long-run and short-run. Thus, it validates the non-existence of the resource curse hypothesis. Moreover, since the government’s share of revenues increase with gas prices, the study recommends stimulating more economic growth by promoting more uses of natural gas in other sectors of the economy—i.e., industry, transport and households—where gas prices are high. Tanzania must also soon decide on an export-oriented liquefied natural gas (LNG) project to fetch a competitive gas price.